Bis-[2,6-(2’-Hydroxy-4’-Sulpho-1’-Naphthylazo)]pyridine Disodium Salt as a Spectrophotometric Reagent for the Determination of Cadmium in Tobacco and Tobacco Products - Barman, Banjit; Barua, Sudarsan (Asian Journal of Chemistry, 2010)
Bis-[2,6-(2'-hydroxy-4'-sulpho-1'-naphthylazo)]pyridine disodium salt (HSNP), a water soluble heterocyclic azo dye has been used for the trace determination of cadmium. Bis-[2,6-(2'- hydroxy-4'-sulpho-1'-naphthylazo)]pyridine disodium salt complexes with cadmium(II) to form a purple coloured, water soluble 1:1 complex with molar extinction coefficient (e) 4.9 × 104 L mol-1 cm-1 at 575 nm in the pH range 7.1-9.3. Beer's law is obeyed upto 0.00-4.20 ppm of Cd(II). The optimum concentration range for determination of Cd(II) is 0.10-1.42 ppm with Sandell's sensitivity of 0.00229 μg Cd(II) cm-2. The reagent is found to be highly sensitive and can be compared with other reagents for determination of cadmium. Solutions of tobacco have been prepared by dry ashing method and cadmium was determined in these solutions spectrophotometrically by using HSNP in tobacco and tobacco products like cigarettes and bidis of Indian make. Average cadmium level in these tobacco samples are found in the range of 0.542-0.693 μg/2 g of the sample.